Single-cell transcriptome of Nepeta tenuifolia leaves reveal differentiation trajectories in glandular trichomes - Zhou, Peina; Chen, Hongyu; Dang, Jingjie; Shi, Zunrui; Shao, Yongfang; Liu, Chanchan; Fan, Longjiang; Wu, Qinan (Frontiers in Plant Science, 2022)
The peltate glandular trichomes (PGTs) on Nepeta tenuifolia leaves can secrete and store bioactive essential oils. ScRNA-seq is a powerful tool for uncovering heterogeneous cells and exploring the development and differentiation of specific cells. Due to leaves rich in PGTs, the young leaves were used to isolated protoplasts and successfully captured 33,254 protoplasts for sequencing purposes. After cell type annotation, all the cells were partitioned into six broad populations with 19 clusters. Cells from PGTs were identified based on the expression patterns of trichome-specific genes, monoterpene biosynthetic genes, and metabolic analysis of PGT secretions. The developmental trajectories of PGTs were delineated by pseudotime analysis. Integrative analysis of scRNA-seq data from N. tenuifolia leaves and Arabidopsis thaliana shoot revealed that PGTs were specific to N. tenuifolia. Thus, our results provide a promising basis for exploring cell development and differentiation in plants, especially glandular trichome initiation and development.